Development of a closed loop functional electrical stimulation / Rodney Petrus Balandong - Rodney Petrus, Balandong (2013)
Objectives This report describe the development and technical details of a newly developed Functional Electrical Stimulation (FES) namely FES2013 with a feedback system for psychophysiological study. Materials and Methods Seven pre-determined design criteria (DC1 – DC7) were introduced for the safety and research versatility of the FES. The important components of the proposed design are Arduino Uno as pattern generator, high voltage switch, and integration of voltage to current converter with Wilson current mirror as the driving stage. Results The flexible closed loop FES system was able to supply consistent 0 ~140mA pulsed current, pulse width of 50 ~ 500 micro second, pulse repetition rate of 50 ~ 100 Hz and functionally monophasic or biphasic pulses based on the preconfigured knowledge embedded in the feedback system. The skin model show that the FES2013 had below 0.3% tolerance as a result of the output current deviation. Theoretically, all the seven design criteria were met. Conclusion The FES2013 is ideally suited for research purposes due to the safe design, having the flexible closed loop operating condition capability, easy coding of Arduino Uno and cheaper than commercial FES system. The circuit and software coding details are provided.